2011
DOI: 10.1371/journal.pone.0014644
|View full text |Cite
|
Sign up to set email alerts
|

Potency, Efficacy and Durability of DNA/DNA, DNA/Protein and Protein/Protein Based Vaccination Using gp63 Against Leishmania donovani in BALB/c Mice

Abstract: BackgroundVisceral leishmaniasis (VL) caused by an intracellular protozoan parasite Leishmania, is fatal in the absence of treatment. At present there are no effective vaccines against any form of leishmaniasis. Here, we evaluate the potency, efficacy and durability of DNA/DNA, DNA-prime/Protein-boost, and Protein/Protein based vaccination against VL in a susceptible murine model.Methods and FindingsTo compare the potency, efficacy, and durability of DNA, protein and heterologous prime-boost (HPB) vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 60 publications
(58 reference statements)
2
40
0
Order By: Relevance
“…This protein is the most abundant cell surface protein during the promastigote stage of the parasite and is attached to the membrane by a glycosylphosphatidylinositol anchor [37-40]. The protective effects of gp63 immunization have been recently demonstrated using various vaccine formulations by many researchers [41,42]. In fish pathogenic haemoflagellates Cryptobia spp., metallopeptidase activity was only found in the pathogenic strain of C. salmositica , its activity decreased significantly with long-term in vitro culture, and the purified metallopeptidases could lyse fish red blood cells [43-45].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is the most abundant cell surface protein during the promastigote stage of the parasite and is attached to the membrane by a glycosylphosphatidylinositol anchor [37-40]. The protective effects of gp63 immunization have been recently demonstrated using various vaccine formulations by many researchers [41,42]. In fish pathogenic haemoflagellates Cryptobia spp., metallopeptidase activity was only found in the pathogenic strain of C. salmositica , its activity decreased significantly with long-term in vitro culture, and the purified metallopeptidases could lyse fish red blood cells [43-45].…”
Section: Discussionmentioning
confidence: 99%
“…This protease proved to be essential in the development and survival of parasite into sandfly gut, because it degrades hemoglobin and other proteins in the blood meals, thereby providing nutrients needed for the growth of promastigotes and protects promastigotes from degradation by the midgut digestive enzymes (Hajmová et al, 2004). Besides all the functions of Gp63 in Leishmania-hosts interactions, the native protein, recombinant or specific peptides from this cleavage was able to elicit a protective immunity to many species of Leishmania infection in a variety of animal models (Handman, et al, 1990;Abdelhak et al, 1995;Bhowmick et al, 2008;Mazumder et al, 2011). The immunogenicity and antigenicity of gp63 is very well known.…”
Section: (L) Infantum and L (L) Tropica Cause Cutaneous And Mucmentioning
confidence: 99%
“…One of the characterised immunogenic proteins in all Leishmania species is Leishmania gp63 or leishmanolysin [16]. It has been shown that vaccination based on gp63 DNA or recombinant gp63 protein is potential to induce T cell stimulation against Leishmania in human producing high levels of INF-γ from effector T cells [27,28]. Our previous studies also proved the immunogenicity of peptides predicted for either class I or II derived from this protein [29,30].…”
Section: Discussionmentioning
confidence: 90%